Identity Construction in the Linguistic Landscape of Charsadda - Raziq, Mehtab; Shah, Mujahid (Pakistan Languages and Humanities Review, 2025)
This study intends to investigate the linguistic landscape of District Charsadda and the role LL plays in the construction of social identity. The display of languages in public spaces is referred to as Linguistic Landscape. Particular languages’ prominence and presence in public settings are crucial indicators of their ethnolinguistic viability in a given community. To achieve this the data is gathered through first-hand fieldwork. A total of 40 pictures were collected and analyzed. The analysis of these pictorial representations of the LL of Charsadda highlights the four more vastly used languages in and around the area concerning the project at hand, namely: Pashto, Urdu, Arabic, and English written, each defining the local community through their language preferences. The data collected through these samples clarify the prospects of LL, building a community’s identity, choice of language varieties, the priority of language, and many social factors like ethnicity and cultural heritage of individuals living in this particular region. The results show that the Linguistic Landscape of Charsadda indicates multilingualism and that Urdu is widely used in the Linguistic Landscape due to social factors. The field of linguistic landscape is a very interesting tool to determine multiple perspectives such as social identity, individual preferences, and even linguistic imperialism. This particular study delves into the interesting region of Charsadda and finds that the language most spoken is actually the one missing by a majority from the vast numbers of advertisement posters, billboards, signposts, and chalked-up walls. This leaves a lot of room for further input by interested scholars.